Clinical outcomes following reperfusion therapy in acute ischemic stroke patients with infective endocarditis: a systematic review. (5th January 2022) - Maheshwari, Rohan; Cordato, Dennis J.; Wardman, Daniel; Thomas, Peter; Bhaskar, Sonu M. M.
Background: Acute ischemic stroke (AIS) is a common and fatal complication of infective endocarditis (IE); however, there is a lack of understanding regarding treatment efficacy. This systematic review aimed to evaluate the safety and efficacy of intravenous thrombolysis (IVT) and endovascular thrombectomy (EVT) in IE patients experiencing AIS. Objectives: The aim of this study was to perform a systematic review investigating the outcomes of AIS in IE patients receiving IVT and/or EVT as a treatment method and to evaluate the safety and efficacy of these methods of reperfusion therapy. Design: A systematic review in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines was conducted. Data Sources and Methods: The EMBASE, Cochrane, and PubMed databases were searched for literature published between 2005 and 2021 investigating outcomes of reperfusion therapy post-AIS in IE and non-IE patients. Descriptive statistics were used to describe the overall frequency of clinical outcomes, and groupwise comparisons were performed using Fisher's exact test to assess the significance of groupwise differences. Results: Three studies were finally included in the systematic review. A total of 13.5% of IE patients compared to 37% of non-IE patients achieved a good functional outcome (modified Rankin Scale score≤ 2) ( P < .001). Furthermore, a larger percentage of the IE cohort achieved good functional outcomes after EVT (22.0%) compared to IVT (10.4%) ( P = .013). The IE cohort also had a higher 3-month postreperfusion mortality rate (48.8%) compared to the non-IE cohort (24.9%) ( P < .001). The rate of intracranial hemorrhage (ICH) postreperfusion was also significantly higher in the IE cohort (23.5%) than in the non-IE cohort (6.5%) ( P < .001). Conclusion: AIS patients with IE, treated with IVT, EVT, or a combination of the two, experience worse clinical and safety outcomes than non-IE patients. EVT yielded better functional outcomes, albeit with higher postreperfusion ICH rates, than IVT.